Spiral bandwidth of four-wave mixing in Rb vapour. Issue 1 (December 2018) - Offer, R.; Stulga, D.; Riis, E.; Franke-Arnold, S.; Arnold, A.
Abstract Laguerre-Gauss beams, and more generally the orbital angular momentum of light (OAM) provide valuable research tools for optical manipulation, processing, imaging and communication. High-efficiency frequency conversion of OAM is possible via four-wave mixing in rubidium vapour. Conservation of the OAM in the two pump beams determines the total OAM shared by the generated light fields at 420 nm and 5.2 μm—but not its distribution between them. Here we experimentally investigate the spiral bandwidth of the generated light modes as a function of pump OAM. A small pump OAM is transferred almost completely to the 420 nm beam. Increasing the total pump OAM broadens the OAM spectrum of the generated light, indicating OAM entanglement between the generated light fields. This clears the path to high-efficiency OAM entanglement between widely disparate wavelengths. The orbital angular momentum (OAM) of light is used in many applications and has the potential to increase the bandwidth of classical and quantum communication. The authors quantitatively investigate the way OAM is distributed between the fields of different wavelength generated from a four-wave mixing process in Rb vapour.